GELIAT ECOFEMINISME PEDESAAN DALAM PELESTARIAN LINGKUNGAN (Studi Kasus Di Desa Curug Muncar Pekalongan) - Rismawati, Shinta Dewi; Thoha, Irham Baihaqii; Sasongko, Supomo Ari (UIN Sunan Kudus, 2017)
ABSTRACTEnvironmental conservation issues always take the woman existence behind. Meanwhile, they have strategic contributions on it. This paper aims to reveal the approach and the reason for the implementation of women's empowerment in environmental conservation in order to support environmental conservation in Curug Muncar Pekalongan. The method of this research is qualitative and the approach method is participatory action research. The first reasons for justifying the implementation of women's empowerment activities are based on the need assessment of the multidimensional existence (ecological, psychological, economic and social) vulnerabilities. The second reason reveal that the sustainability of women's empowerment is by applying three pillars of sustainable. It synergize the ecological, economic and social dimension. It mobilize Kelompok Perempuan Peduli Dalam Pelestarian Lingkungan (P3L) in this region to care for environmental conservation. Keywords:ecofeminism, participatory action research, sustainability development, sak uwong sak uwit programs.